Discursive Constructions of Communicative Rationality in Kenyan Presidential Election Petitions of 2022 at the Supreme Court of Kenya - Ngaiza, Asteria Gabriel; Malima, Masatu Julius (Universitas Lancang Kuning, 2023)
How communicative rationality is constructed and shared among interlocutors in a court in the seeking of justice, given the background of distrust in the Kenyan Presidential Election context, gave attention to this study. The study investigated the construction of communicative rationality in the courtyard. The study assessed the types of illocutionary forces and their discursive legal practices and determined how interlocutors redeem the illocutionary logic in the courtyard. A documentary review of the written judgment of Ruto against Odinga in the presidential election of 2022 was used as the data collection method. The analytical frameworks involved Austin's (1962b) Speech Act theory and Searle and Vanderveken's (1985) illocutionary commitments. The findings showed that petitioners chose illocutionary forces to downgrade respondents' claims. The discursive nature of their legal practices was characterized by a lack of fairness, transparency, and integrity of IEBC and its Chairperson. Respondents used illocutionary forces, including denials, for face protection and repair. Their discursive legal practices were characterized by compliance, transparency, and accountability to win the Court's decision. Petitioners and respondents used much propositional content, modes of achievement, and preparatory conditions to construct their validity claims. In achieving justice, the group of Judges must consider interlocutors' presentations of credible statements of truth and acceptable normative statements of legal practices. A group of Judges needs to take precautions against the interlocutors' tricks and manipulation of the Constitution for effective decision-making.